THE ROLE OF THE STATE IN THE MARKET ECONOMY - Jurayeva Zahro Khusniddin qizi (Bright Mind Publishing, 2026)
This article analyzes the role of the state in a market economy and its impact on economic processes. It justifies the necessity of government intervention to address the shortcomings of the market mechanism alongside its advantages. The article examines the instruments of state economic policy — fiscal, monetary, price, and foreign trade policies. Using the example of Uzbekistan, it also analyzes the active role of the state in deepening market reforms, fostering a competitive environment, and ensuring social justice.
Keywords: Market mechanism, fiscal policy, monetary policy, prices, foreign trade, competition, equilibrium, stability, efficiency.